Search for Key Genes and Functional Pathways of Ulcerative Colitis to Colon Cancer Based on Bioinformatics - Wang, Shengbao; Zhen, Lingling; Li, Xiaoli; Fu, Xu; Li, Peiwu; Zhang, Dekui (Frontiers in Oncology, 2022)
Ulcerative colitis (UC) is a persistent and diffuse inflammatory disease of the intestine. It is widely prevalent in developed countries. Approximately 30% of patients with UC suffer from widespread and aggressive colitis and are at increased risk of colon cancer. In this study, the genetic features and potential molecular mechanisms shared between UC and colorectal cancer were investigated. The datasets from GEO and TCGA were analyzed to obtain differentially expressed genes, of which there were 116 overlapping genes. A module containing 15 genes was obtained using String and Cytoscape to analyze the module and identify hub genes. Weighted gene co-expression network analysis (WGCNA) was used to identify co-expression modules associated with UC and colon cancer, with 52 overlapping genes. Functional clustering of the two gene cohorts was performed using the Metascape online tool, with three significant functions or pathways associated with both gene cohorts. A total of 19 key genes were included, and CCT2 was identified after expression and survival analyses. CCT2 is highly expressed in colon cancer and lowly expressed in UC, and its low expression is associated with a poor prognostic ratio. This study reveals, for the first time, that CCT2 may be a promoter of UC transformation into colon cancer and identifies new gene candidates that could be used as biomarkers or potential therapeutic targets.